Adherence to Antiretroviral Therapy and Virologic Failure - Bezabhe, W.; Stafford, Leanne; Bereznicki, L.; Peterson, G. (Wolters Kluwer Health, Inc., 2016)
© 2016 Wolters Kluwer Health, Inc. All rights reserved.The often cited need to achieve =95% (nearly perfect) adherence to antiretroviral therapy (ART) for successful virologic outcomes in HIV may present a barrier to initiation of therapy in the early stages of HIV. This meta-analysis synthesized 43 studies (27,905 participants) performed across >26 countries, to determine the relationship between cut-off point for optimal adherence to ART and virologic outcomes. Meta-analysis was performed using a random-effect model to calculate pooled odds ratios with corresponding 95% confidence intervals. The mean rate of patients reporting optimal adherence was 63.4%. Compared with suboptimal adherence, optimal adherence was associated with a lower risk of virologic failure (0.34; 95% CI: 0.26-0.44). There were no significant differences in the pooled odds ratios among different optimal adherence thresholds (=98-100%, =95%, =80-90%). Study design (randomized controlled trial vs observational study) (regression coefficient 0.74, 95% CI: 0.04-1.43, P<0.05) and study region (developing vs developed countries; regression coefficient 0.56, 95% CI: 0.01-1.12, P<0.05) remained as independent predictors of between-study heterogeneity, with more patients with optimal adherence from developing countries or randomized controlled trials experiencing virologic failure. The threshold for optimal adherence to achieve better virologic outcomes appears to be wider than the commonly used cut-off point (=95% adherence). The cut-off point for optimal adherence could be redefined to a slightly lower level to encourage the prescribing ART at an early stage of HIV infection.